The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/00302228211009754
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Death for Nursing Students and Their Attitudes Toward Dignified Death Principles

Abstract: This study aims to determine the meaning of death for nursing students and their attitudes toward dignified death principles. The descriptive study was conducted with nursing students studying at a state university in Turkey. The data were collected using the Personal Information Form, the Personal Meanings of Death Scale (PMDS), and the Assessment Scale of Attitudes toward the Principles of Dying with Dignity (ASAPDD). A positive and low-level significant relationship was determined between the students' age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…Positive attitudes and perceptions about death with a focus on dignity and what constitutes a good death reflect a caring culture in nurses working in VA facilities. The mean score of the ASAPDD, principles of dying with dignity, was 57.01, which was higher than those of nursing students 6,7 and ICU nurses, 11 and more than twice as high as those of oncology nurses 15 …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Positive attitudes and perceptions about death with a focus on dignity and what constitutes a good death reflect a caring culture in nurses working in VA facilities. The mean score of the ASAPDD, principles of dying with dignity, was 57.01, which was higher than those of nursing students 6,7 and ICU nurses, 11 and more than twice as high as those of oncology nurses 15 …”
Section: Discussionmentioning
confidence: 78%
“…The mean score for the Assessment Scale of Attitudes Toward Principles of Dying with Dignity (ASAPDD) was 47.7 ± 8.1, and it was moderately correlated with spiritual care ( r = 0.40, P = .00). Bilgiç 7 found that Turkish nursing students (N = 593) who had the opportunity to care for patients who died during their care had significantly higher means or more positive attitudes toward the principles of dying with dignity than those who did not ( P = .00). The mean ASAPDD score was 46.29 ± 7.64, with a low positive correlation with age ( r = 0.098, P = .030).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Não obstante, nesta conjuntura, há algumas barreiras mencionadas pelos profissionais da saúde como falta de tempo, de conhecimento e medo de impor suas próprias crenças, o que aponta uma insegurança e a necessidade de treinamento com relação à temática 39 . A reflexão sobre o processo de morte e morrer permite os estudantes e profissionais da saúde a dar sentido a esta experiência em diferentes esferas, ainda mais por verem o processo como parte integrante do ciclo vital humano, como evento inerente, percepção que se reflete nos aspectos social, espiritual e ético, enriquecendo o cenário no cuidado profissional de enfermagem 14,15 .…”
Section: Discussionunclassified
“…Na temática, há algumas publicações que abordam o tema, como a atitude de profissionais da saúde frente à morte e seus significados 14,15 , a atitude de pacientes em cuidados paliativos frente à morte na atenção domiciliar 16 , as necessidades dos pacientes em cuidados paliativos com câncer diante do processo de morte e morrer 3 , a morte para cuidadores familiares 17 , e o que uma morte boa seria para pacientes oncológicos 18 . Entretanto, este estudo avança em apresentar o significado da morte para os pacientes oncológicos hospitalizados, que, por vezes, testemunham a morte de outros pacientes e que, possivelmente por isso, a sentem mais próxima de si mesmos 19 .…”
Section: Introductionunclassified
“…A qualitative study of 17 nursing students found that providing nursing care for dying patients is difficult and frightening; they view their roles during this situation as mere spectators, and that death is perceived as abstract (Österlind et al, 2016). It was also noted that nursing students who experience death have difficulty accepting and coping (Bilgiç, 2021). Studies have shown that gender influences a person’s death and dying experience (Skulason et al, 2014).…”
Section: Introductionmentioning
confidence: 99%